Logging residue supply and costs for electricity generation: Potential variability and policy considerations. (May 2018) - Baker, Justin S.; Crouch, Adam; Cai, Yongxia; Latta, Greg; Ohrel, Sara; Jones, Jason; Latané, Annah
Abstract: This paper applies a spatial allocation optimization model to evaluate logging residue supply potential and costs for bioelectricity generation within the conterminous United States. Simulations are developed to estimate a range in supply potential and costs across a broad range of sensitivity scenarios, including (1) different biomass availability rates based on observed roundwood removals, (2) renewable energy targets set nationally or at a state-level, (3) with and without biomass sourcing restrictions within a state, (4) with and without access to public lands, and (5) policy restrictions on eligible facility types. Under the least restrictive policy scenario (a hypothetical national mandate), total supply is 8.8 million dry tons (MDT) at 20/DT and increases to 32.5 MDT at 80/DT. Results fall within the range of previous logging residue supply studies in the U.S., including the last two Billion Ton reports. Results from this paper offer important policy insight into the potential cost efficiency of a flexible policy design. Sensitivity scenarios show potential supply cost increases that could result from policies imposing regional restrictions, limiting access to public lands, and restricting eligible facilities. Restricting biomass supply sources within state boundaries reduces total supply up to 10% relative to an unrestricted national policy. Highlights: Logging residues can provide an important renewable energy fuel source. Supply potential varies with the biomass price and regional forest harvests. Eligible facilities and their locations are key determinants of supply costs. Certain policy considerations result in cost inefficiencies and reduced supply.